An Insight Into the World of Artificial Intelligence, Its Effect on the Labor Market, Fears Regarding Its Application - Fecskovics, Melinda (Acta Carolus Robertus, 2024)
The development of Artificial Intelligence is such, if not more significant, for human society than the previous industrial revolutions. Artificial Intelligence systems are able to learn and adapt based on data, whether it is healthcare, education, manufacturing, or company processes. They are able to process and analyze large amounts of data quickly and efficiently, so Artificial Intelligence is suitable for optimizing processes. Errors, the associated costs and the time spent solving them are reduced, daily operations are more efficient. It is almost impossible to find a social area where it is not able to bring about change and development. Development means an opportunity to improve and find new areas, but it also contains dangers. In terms of Artificial Intelligence, rapid, sometimes seemingly untraceable accelerations of development can be observed, which remind ordinary people of the world of sci-fi movies. Scientists, developers, and company managers in certain sectors see it as an exciting research opportunity, while others fear the security of their data, their jobs, and thus their livelihoods just by hearing the word. The impact of Artificial Intelligence is already visible on the labor market. A number of previously unknown jobs have appeared, such as Artificial Intelligence ethics experts, Artificial Intelligence consultants, Artificial Intelligence developers and engineers. However, there are jobs that will be discontinued (bank clerks, postal clerks, administrators, shop assistants). Those who are negatively affected by the change, whether they are employers or employees, try to find a solution in order to preserve their stability. In my study, I present several surveys in which the impact and reception of Artificial Intelligence was examined abroad and at home, and in the conclusions section I collect some proposed solutions for companies and individuals regarding the increasingly confusing situation.